Islamic Accounting and the Sustainable Development Goals: Regulatory Ethics, Financial Inclusion, and the Dual Financial System in Indonesia - Primadhani Dyah Larasati Suyatno; Maulana Ihsan Yusufi Suyatno (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2025)
This study explores the role of Islamic accounting in advancing the Sustainable Development Goals (SDGs) in Indonesia using a qualitative approach. Data were collected through in-depth interviews with 15 informants—academics, regulators, and practitioners—and analyzed using NVivo software. The findings highlight three critical themes: (1) maqasid al-shariah principles are embedded in regulation but constrained by dual regulatory authority, identified 28 times in the coding; (2) Islamic financial inclusion is expanding through profit-sharing contracts, yet low financial literacy emerged 35 times as the most dominant barrier; and (3) the dual financial system fosters innovation but is hindered by public misconceptions (12) and regulatory overlaps (10). These results demonstrate that Islamic accounting goes beyond normative discourse, functioning as an institutional mechanism that bridges regulatory ethics, literacy, and dual systems. The limitations of this study include its small sample size and qualitative scope, suggesting the need for future quantitative validation. The novelty lies in integrating empirical field data with the SDG framework, providing practical implications for regulators, financial institutions, and academia in aligning Islamic accounting with global sustainability goals.